Neurophysiological and Neuroradiological Changes in Children With Chronic Kidney Disease - Abd El Naby, Sameh A.; Bahbah, Wael A.; Kasemy, Zeinab A.; Mahmoud, Asmaa A. (Frontiers in Pediatrics, 2020)
Background: Patients with chronic kidney disease on maintenance hemodialysis are frequently presented by neurological complications. Both central and peripheral nervous system are affected. Common neurological complications in CKD include peripheral and autonomic neuropathies, encephalopathy and stroke. Objective: to detect the neurological manifestations and complications in children with chronic kidney disease through neurological examination, neurophysiological and neuro-radiological findings. Methods: The study included 50 patients with CKD admitted to pediatric nephrology unit. Their history, complete physical and neurological examination finding had been recorded. All of them underwent nerve conduction, electromyography (EMG), electroencephalography (EEG) and magnetic resonance imaging (MRI). Results: Included children were 23 males and 27 females with mean age of (12.08±3.46 year). 11 (22%) patients of end stage renal disease developed polyneuropathy mostly of axonal polyneuropathy pattern while 78% of them showed normal electrophysiological studies. No myopathy was detected. Abnormal electroencephalography findings were detected in 18% of patients in the form of generalized and focal (temporal, occipital and frontal) epileptogenic activity had been found. Abnormal MRI findings were detected in 16% of patients mostly of encephalomalachia. Conclusion: Neurological status in children with maintenance hemodialysis end stage renal disease was impaired. Uremic neuropathy is highly prevalent in these patients. They developed polyneuropathy mostly of axonal polyneuropathy pattern. EEG is a useful method for early recognition of subclinical uremic encephalopathy and/or epileptogenic activity. Early demonstration and management of uremic neurological conditions may decrease the physical disability in children with CKD.